2015
DOI: 10.1371/journal.pone.0132225
|View full text |Cite|
|
Sign up to set email alerts
|

miR-203 Acts as a Tumor Suppressor Gene in Osteosarcoma by Regulating RAB22A

Abstract: microRNAs (miRNAs), small noncoding RNAs of 19–25 nt, play an important roles in the pathological processes of tumorigenesis. The object of this study was to study the expression and function of miR-203 and to found its target gene in osteosarcoma. In our study, we found the expression level of miR-203 was significantly downregulated in osteosarcoma cell lines and tissues. In addition, overexpression of miR-203 inhibited the osteosarcoma cell proliferation and migration and inhibited Mesenchymal-to-Epithelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 46 publications
3
27
0
Order By: Relevance
“…These findings suggest that the upregulation of RAB22A in melanoma may partly be due to the decreased expression of miR-203. In fact, the targeting relationship between miR-203 and RAB22A was also reported in osteosarcoma [13]. Therefore, our study expands the importance of miR-203/RAB22A axis in human cancers.…”
Section: Discussionsupporting
confidence: 75%
“…These findings suggest that the upregulation of RAB22A in melanoma may partly be due to the decreased expression of miR-203. In fact, the targeting relationship between miR-203 and RAB22A was also reported in osteosarcoma [13]. Therefore, our study expands the importance of miR-203/RAB22A axis in human cancers.…”
Section: Discussionsupporting
confidence: 75%
“…Zhang et al found that miR-373 targeting of the Rab22a oncogene suppressed tumor invasion and metastasis in ovarian cancer (30). miR-203 has been reported as a tumor-suppressor gene in osteosarcoma by regulating RAB22A (31). The present study identified that miR-204 inhibited RAB22A expression by directly targeting 3'UTR of RAB22A in RCC.…”
Section: Discussionsupporting
confidence: 56%
“…miR-203 also plays important roles in cancerigenesis. miR-203 has been reported to be the tumor suppressor in osteosarcoma (29). miR-203 also directly targeted oncogene ADAM9 and long non-coding RNA HULC to inhibit the hepatocellular carcinoma cell proliferation and metastasis (30).…”
Section: Discussionmentioning
confidence: 99%